DNA methylation patterns in aging and aging phenotypes - Guarasci, Francesco; Bellizzi, Dina; Cerra, Maria Carmela (My University, 2019)
During my PhD program, my work has been addressed to the study of the role of epigenetic modifications in aging and in age-related phenotypes. Epigenetics is the study of changes in gene expression that do not involve changes to the underlying DNA sequence. These changes affect cellular phenotypic expression by regulating relative gene expression levels. They are a common and natural process in living cells and are tightly controlled by pre-programmed mechanisms. Epigenetics modifications can be influenced by multiple factors including environmental conditions, lifestyle, nutrition, use of drugs, disease state and age. Patterns of DNA methylation, the best known and characterized epigenetic modification, change during aging; indeed, with increasing aging, genome-wide methylation levels decrease, meanwhile genomic regions, including CpG islands, become more methylated. Analyses of the above patterns provided new perspectives for establishing powerful biomarkers of human aging which have the potential to generate accurate prediction not only of the chronological but also of the biological age. The first section of the PhD thesis consists in a comprehensive overview of the general features of DNA methylation and its implication in age and age-related diseases. The topic is addressed referring to the methylation patterns established not only at nuclear but also at mitochondrial genome level. In addition, the influence of a number of environmental factors on the above patterns is also discussed. In the second section, an original research work, carried out in order to identify novel biomarkers of aging, is reported. In this work, methylation status of nuclear genes involved in mitochondrial fusion, fission, biogenesis and mitophagy, fundamental components of the mitochondrial quality control process, was investigated in subjects of different ages of the Calabrian population. The methylation levels of RAB32 and RHOT2 genes were significantly associated with age and, in particular, those of RAB32 even with the risk of developing disability. The study, therefore, led to the identification of two new biomarkers for both chronological and biological aging. In the Appendix, research works already published are reported. The first one concerns the correlation between DNA methylation and nutrition during lifetime. Global DNA methylation profiles were examined in different tissues of rats of different ages, fed with a standard and hypocaloric diet, and their association with aging and nutrition was evaluated. The results obtained have shown that tissue-specific variations in methylation levels occur during aging and that nutrition influences the state of global DNA methylation during the course of life. The hypocaloric diet seems to influence more strongly the epigenetic status of the offspring when administered during the maternal pre-gestational period compared to the gestation and lactation period. Therefore, changes in the global DNA methylation status represent an epigenetic mechanism by which age and nutrition intersect each oth and, in turn, influence the plasticity of aging. The second one is a review on the current advances in mitochondrial epigenetics studies and the increasing indication of mtDNA methylation status as an attractive biomarker for peculiar physiological and pathological phenotypes. It comes from the increasing evidence on the fact that, similarly to nuclear DNA, also mtDNA is subject to methylation and hydroxymethylation and these modifications are influenced by multiple environmental factors.
Dottorato di Ricerca in Scienze della Vita, Ciclo XXXI
Keywords: Aging; Genetics; Aging; Physiology; DNA; Methylation